ONLINE MARKETING MEDIA IN THE DIGITAL AGE: THE DEMISE OF CONVENTIONAL RETAIL MARKETS - Zainul Wasik; Kuncoro Catur Nugroho; Dedy Iswanto (PT. Mawadaku Sukses Solusindo, 2023)
Introduction - Online marketing has experienced significant growth in the digital era, and its impact on the conventional retail market has been a hot topic of discussion. Based on the data obtained, from late 2017 to early 2018 was the beginning of the modern retail market turmoil. One by one, modern retail markets fell because modern society no longer wants safe and convenient shopping activities, but also practical and efficient. This is offered by online shopping, the various benefits obtained, making shoppers prefer online shopping activities over conventional shopping. Online marketing provides greater accessibility to consumers. They can shop anytime and anywhere through their electronic devices. Objective - The researcher intends to deepen the study to explore and analyze the exposure of the digitalization era of online marketing media on the fall of conventional retail markets. The purpose of this study is of course to find out and analyse the incessant exposure of the digitalisation era, especially marketing media in its role in bringing down the conventional retail market. Design/Methodology/Approach - This research uses a qualitative descriptive method, which is contextual research that makes informants instruments and is adjusted to a natural situation about data collection which is generally qualitative. Research procedures produce descriptive data in the form of written or spoken words of people and observable behavior. Finding - People tend to spend online shopping activities rather than doing conventional shopping activities. The impact is the fall of the conventional market, the glory of the conventional market is gradually starting to erode and is predicted to experience massive closures in the future. There are many advantages of shopping online rather than conventionally. Business leaders need to develop an integrated marketing strategy between online and offline platforms. Recognizing how both can support each other and increase overall brand visibility will be the key to success.